Melejitkan Ghiroh Belajar Santri Melalui Budaya Literasi di Pesantren - Baharun, Hasan; Rizqiyah, Lailatur (TADRIS: Jurnal Pendidikan Islam, 2020)
This paper aims at analyzing and understanding the efforts of pesantren in increasing the students’ ghiroh to learn through literacy culture in pesantren. With ghiroh of learning, it is expected that students can carry out learning well. Ghiroh learning is a measurement for learning success. By forming good Ghiroh on students, it is able to form good behaviors especially forming and applying literacy culture in pesantren, in the form of reading and writing. Literacy culture in pesantren is a habitual activity that is practiced by students by reading, writing and producing an art work. This research uses a qualitative approach with case study type. The research site is Pondok Pesantren Lubbul Labib, Maron, Probolinggo. The results showed that the efforts to increase the student’s motivation through literacy culture in pesantren were carried out through: 1) INTISHOB program (Inti'as Fi Shobah) or giving encouragement in the morning, 2) study groups, 3) cultural orientation, 4) providing library and e-library facilities, and 5) learning evaluation. Through these efforts, the literacy culture of santri has developed well in Pondok Pesantren Lubbul Labib, Maron, Probolinggo